Electrophysiological responses to dopamine of rat hypophysial cells in lactotroph-enriched primary cultures. - Israel, J M (1987)
1. Cells from 14-day-old and lactating female rat pituitary glands were dissociated, separated and enriched on a continuous gradient of bovine serum albumin at unit gravity. They were maintained for at least 6 days in culture before perifusion and electrophysiological experiments were performed. 2. Immunofluorescent staining of the resulting gradient fractions (numbered F2 to F9) from both groups of animals indicated that the majority of lactotrophs were located in the light fractions (F3-F4). However, a second population of lactotrophs was observed in the heavy fractions (F7-F9) isolated from lactating females. 3. Basal secretion rates of prolactin were in the order of 2-40 ng 2 min-1 10(6) cells-1 and were inhibited by dopamine in a dose-dependent manner. 4. According to their electrophysiological properties, cells from 14-day-old females (first group) were categorized as follows: (1) inexcitable cells, which displayed a low resting potential of about -35 mV (39% of cells tested, n = 118); and (2) excitable cells, which displayed either triggered or spontaneous action potentials and resting membrane potentials higher than -50 mV (61% of cells tested, n = 185). 5. In the light fraction from lactating females (second group), the majority of the cells were excitable (70%) and showed high resting membrane potentials (-50 to -55 mV) and 15% of these cells displayed spontaneous action potentials. 6. Heavy fractions (third group) contained a high percentage of non-spontaneous but excitable cells (80% of the cells tested, n = 65). These cells were able to elicit action potentials after the cessation of hyperpolarizing current pulses ('off' potentials). 7. Action potentials were insensitive to the sodium channel blocker, tetrodotoxin (TTX; 5 x 10(-6) M) but were reversibly blocked by calcium channel blockers such as cobalt, manganese and cadmium (10 mM). 8. In excitable cells from the three groups, dopamine (10(-7) M) induced a hyperpolarizing response due to an increase of the membrane conductance. During this response, action potentials were inhibited. It was shown that this was not a direct effect of dopamine. The reversal potential of the dopamine-induced response in these cells was found to be at -100 mV. This value was shifted to more positive potentials (-50 mV) when high-potassium medium was used (56 mM). 9. In non-excitable cells (first group), dopamine (10(-7) M) induced a hyperpolarizing response due to a decrease of the membrane conductance.(ABSTRACT TRUNCATED AT 400 WORDS)